Modeling and Simulation of Inverter based Distributed Generators for Renewable Energy Integration⁎. Issue 4 (2019) - Macana, Carlos A.; Pota, Hemanshu R.; Hossain, Md Alamgir
Abstract: The challenges and potential solutions in modeling and simulation for the new distribution grids with high penetration of inverter interfaced distributed generators including wind and photovoltaic generators are presented in this paper. A dq0 dynamic model for grid-connected Current Source Inverters (CSI) with power control is developed and validated in two different simulation studies. In this way, Electromagnetic transient (EMT) and phasor (PS) simulations are performed for a simple case of a CSI connected to the grid. A modified 13-nodes IEEE distribution test system with photovoltaic and wind based distributed generation is performed to extend the results to a standard distribution test system. Accuracy and reliability problems can be inferred from the simulation results if the network dynamics are neglected, and the need to develop new simulation models for the new emerging distribution grids is shown.